Relationships between Emotional Intelligence and Organizational Commitment and Job Performance among Administrators in a Malaysian Public University - Md. Yusof, Rozman (2007)
The individual performance is an issue of growing importance to the higher learning institutions in their preparation to accomplish their mission to become a world class university. An employee commitment, together with a competent workforce seemed to be of decisive importance for a university to be able to compete in quality and to go along with changes. At present, the theoretical linkages between job performance and both emotional intelligence and organizational commitment simultaneously in the higher learning institution are not fully established by past researchers. Therefore, it is the aim of this study to investigate the relationship of the selected independent variables: emotional intelligence dimensions (self-management, relationship-management and communication), organizational commitment dimensions (affective commitment, continuance commitment and normative commitment) and job performance, determined the significant difference in job performance between each group of administrators in UiTM; and finally, determined the predictor variables of job performance. Data were collected from 152 randomly selected administrators from a public university, using self-administered questionnaires that comprised: (1) Management View/Practices Questionnaire (100 items) that measured job performance; (2) PeopleIndex (74 items) that measured emotional intelligence; and (3) Organizational Commitment Questionnaire (18 items) that measured organizational commitment. Overall, the study revealed that the administrators’ job performance and its dimensions were high. The level of emotional intelligence and its dimensions: self-management, relationship-management and communication were relatively high. Their level of organization commitment was moderate. However, they were reported high level of affective commitment, moderate level of continuance commitment but low level of normative commitment. One-way ANOVA test revealed that there was a significant job performance difference within workload level of administrators. Posthoc Turkey test also revealed that there was a significant job performance difference between age group 20-29 years old and age group > 49 years old as it increased progressively for each older age group. Results obtained from the correlation analysis revealed that the three emotional intelligence dimensions of the administrators were strongly related to job performance. Affective commitment was moderately positive related to job performance and continuance commitment was also found to be positive but low. However, normative commitment was found to be negatively related to job performance. The result of the multiple regression analysis at .05 level of significant showed that communication, affective commitment and relationship-management were significant predictors of job performance of employees. These three predictors explained 64% of the variance in job performance of the administrators. This study has implications on the importance of recognizing other dimensions of the job performance construct such as emotional intelligence and organizational commitment in order to provide a more comprehensive account of what constitutes performance. In reviewing the overall results of the study, it would appear to provide tentative evidence which suggests that the administrators may achieve improved performance if the emotional intelligence elements of relationshipmanagement and communication are included in their selection criteria. Furthermore, having established the positive influence of affective commitment on job performance will become important for organizations to find out what they can do to maintain and enhance the commitment of these employees as part of their internal marketing strategy. Therefore, the results of the study had recognized the existence of emotional intelligence and components of commitment especially affective commitment in the workplace. This has clear implications for a university to target relevant strategies if they want to achieve better performance among administrators. Finally, the study recommends among other things that the organizations should provide a proper training on emotional intelligence and organizational commitment to administrators to enable them to perform their job better. This study should also be extended to include a larger population of administrators from other universities in Malaysia so that it would be able to provide stronger evidence on the applicability of western findings in Malaysia.